2016
DOI: 10.5812/ircmj.41873
|View full text |Cite
|
Sign up to set email alerts
|

Association of Osteoprotegerin with Obesity, Insulin Resistance and Non-Alcoholic Fatty Liver Disease in Children

Abstract: BackgroundOsteoprotegerin (OPG) is a member of the tumor necrosis factor superfamily. Reduced OPG levels are related to obesity, insulin resistance, and non-alcoholic fatty liver disease (NAFLD).ObjectivesThe aim of this study was to evaluate the relationship between OPG levels, obesity, insulin resistance, and NAFLD in pediatric patients.MethodsThis was a prospective, cross-sectional, controlled study that was conducted in the department of pediatrics at Bagcilar training and research hospital in Istanbul, Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
4
16
0
Order By: Relevance
“…Two previously published studies, involving a smaller number of adolescents ( n = 98) [13] and adults ( n = 74) [31], respectively, found associations of osteoprotegerin levels with fasting insulin and HOMA-IR, which we did not observe. Our results are consistent with those of Erol et al [14] in 174 children and adolescents; they failed to find an association of osteoprotegerin with HOMA-IR. Though there is a relationship between osteoprotegerin and liver fat in adults [11] which constitutes a risk factor for insulin resistance, the relevance of this bone marker for glucose metabolism, particularly in children and adolescents, remains unclear and is probably minimal.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Two previously published studies, involving a smaller number of adolescents ( n = 98) [13] and adults ( n = 74) [31], respectively, found associations of osteoprotegerin levels with fasting insulin and HOMA-IR, which we did not observe. Our results are consistent with those of Erol et al [14] in 174 children and adolescents; they failed to find an association of osteoprotegerin with HOMA-IR. Though there is a relationship between osteoprotegerin and liver fat in adults [11] which constitutes a risk factor for insulin resistance, the relevance of this bone marker for glucose metabolism, particularly in children and adolescents, remains unclear and is probably minimal.…”
Section: Discussionsupporting
confidence: 93%
“…In several studies, serum osteoprotegerin has been found to increase with liver fat content [11], and osteoprotegerin levels are higher in adults with diabetes or prediabetes than in those with normal glucose tolerance [12]. In obese adolescents, there was a positive correlation of osteoprotegerin with several parameters of insulin resistance (i.e., fasting serum insulin and HOMA-IR) [13], which was, however, not confirmed by another study including children and adolescents [14]. Another study [15] found that osteoprotegerin levels increased parallel with the physiological increase of insulin resistance during puberty [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that obese subjects showed significantly lower OPG levels respect to the controls (3335); however no correlation has been reported between OPG and BMI (36, 37). Otherwise, few studies measured higher levels of OPG in obese subjects compared with the controls (38, 39).…”
Section: Discussionmentioning
confidence: 86%
“…This study was demonstrated fatty liver a high frequency seen in obese children and it was more frequency seen in cases with MS. Anthropometric measurements and BIA results was moderately correlated in obese children. Different studies have reported the prevalence of fatty liver in obese children to range from 24%-58% [15,16]. Although liver biopsy is the gold standard in the diagnosis of fatty liver, its invasive application prevents it from being used routinely as a diagnostic method [17].…”
Section: Discussionmentioning
confidence: 99%